2020
DOI: 10.1111/jan.14387
|View full text |Cite
|
Sign up to set email alerts
|

The nurse’s experience of decision‐making processes in missed nursing care: A qualitative study

Abstract: Aims To explore nurses’ perspectives regarding the decision‐making processes that lead to missed nursing care and to identify the personal and contextual attributes involved in these processes. Design A qualitative study was undertaken between April – October 2018. Methods A total of 28 registered nurses working in different wards in hospital settings participated in nine focus groups with semi‐structured interviews. An interview guide encouraged nurses to share perceptions of missed care and the personal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…Also, another study conducted in Iran in 2018 mentioned that delays in accessing prescribed medications during one shift lead to prescribing medications in the next shift ( 18 ). Abdelhadi et al also admitted that nurses delayed care they thought was urgent ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study conducted in Iran in 2018 mentioned that delays in accessing prescribed medications during one shift lead to prescribing medications in the next shift ( 18 ). Abdelhadi et al also admitted that nurses delayed care they thought was urgent ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well understood that within hospital environments, nurses often face short staffing and pressure to be efficient as result of cost containment (Cho et al, 2018;Griffiths et al, 2019Griffiths et al, , 2021Suhonen et al, 2018). Hospital contexts are ever changing, chaotic, fast paced, with complex challenges (Abdelhadi et al, 2020;Bjork & Hamilton, 2011;Krishnam, 2018;Muntean, 2012;Thompson et al, 2013). Thus, it would follow that to survive shift by shift, nurses must rely heavily on fast thinking, with little time provided to engage in slow, critically reflective thinking.…”
Section: The Influen Ce Of Conte X T In Nur S E S Decis Ion -Makingmentioning
confidence: 99%
“…Care rationing is doing good enough to get through the shift with a workload perceived as unwieldy. Abdelhadi et al (2020) identified three themes influencing missed nursing care: the role of the nurses' agency in explicit/implicit rationing; automated thinking in routine situations with effort thinking reserved for more novel situation; and situational triggers, such as difficult tasks, patients perceived as difficult or, the presence of others such as patient family or an authority figure such as a head nurse. This parallels Kahneman's (2011) explanation of how fast thinking is used predominantly in routine situations and slow critical thinking is reserved for new or challenging situations.…”
Section: Dang Er S Of Nur S E S Thinking Fa S T With Older Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed Kalisch et al.’s (2009) own widely cited concept analysis of MNC indicates that the antecedents to MNC involve workforce, resources, communication and teamwork, which are then coupled with elements of the nursing process and the internal perceptions and values of the nurse. More recent work echoes this complexity, whether they are exploring prevalence and predictors of MNC (Jones et al., 2015) or qualitative work examining the contribution of nurses’ decision-making processes to MNC (Abdelhadi et al., 2020) or the role of effective leadership and supportive relationships being central to the influence of nurse managers on MNC (McCauley et al., 2020).…”
mentioning
confidence: 99%